(untitled) (Research, Society and Development, 2020)
In this paper, we describe a case study of the school process of a deaf student (DS) in the Elementary School located in Macapá, Amapá, mediated by Specialized Educational Service (SES) practices. The accompanied student is an 11 years-old female, which has been studying at school since the 1st year and currently enrolled and attending the 5th grade. According to her father, she is the firstborn daughter, wore a hearing aid and did not get used to it, participated in speech therapy sessions and did not develop oralization. However, he did not know how to report his daughter’s degree of deafness. At school, the student attends the Multifunctional Resource Room (MRR), where she receives the SES, in Brazilian Sign Language (LIBRAS, L1) and Portuguese Language (L2) three times a week, during the daytime. Develops written activities and games with visual and computer resources, in a contextualized way. The communication problem at school and family was solved by developing a project in the classroom once a week, and on Saturdays with school staff and the student’s father. The regular teacher introduced LIBRAS and the use of images in the common classroom; the students and the teacher started interacting in LIBRAS. Therefore, the communication barrier was eliminated and teaching in L1 and L2 became accessible and meaningful.